A narrative review of pharmacy workforce challenges in Indonesia - Sherly Meilianti; Felicity Smith; Afina Nur Fauziyyah; Nisa Masyitah; Franciscus Kristianto; Desak Ketut Ernawati; Rasta Naya; Ian Bates (Human Resources for Health)
Abstract Background Developing a skilled and motivated pharmacy workforce is imperative for strengthening healthcare systems. This narrative review examines challenges faced by Indonesian pharmacists in practice and identifies strategies and initiatives that have been implemented to support workforce development in Indonesia. Method A systematic search of three databases (PubMed, EBSCO, and OVID) was conducted to identify research articles published from database inception to 30 June 2022. Data were synthesised narratively and mapped to a multidimensional healthcare workforce framework. Result Forty studies were included, revealing four interrelated themes of workforce challenges: (1) personal challenges, (2) workplace conditions, (3) societal contribution and recognition; and (4) regulatory aspects. Strategies identified include professional guidelines, accreditation systems, and competency-based training programmes. Conclusion The review indicates a need for Indonesian pharmacists to enhance their competencies to provide high-quality services. A multi-sectoral approach is recommended to address challenges. Providing decent working conditions for pharmacists in conjunction with workplace accreditation can support best practices of pharmaceutical care and ensure patient safety.